Neonatal lupus : 5 pediatric cases - Aamri, Hasna; Hazzab, N.; Bennaoui, F.; Slitine, N. El Idrissi; Maoulainine, F. M. R. (British Journal of Healthcare and Medical Research, 2022)
Neonatal lupus erythematosus is a rare condition that manifests itself in different types of damage, whether cutaneous, hepatic, hematological, neurological or even cardiac. We report here three cases of neonatal lupus occurring in newborns, two of them from completely asymptomatic mothers and revealed by cardiac involvement and one case revealed by skin involvement.